Contrast-enhanced ultrasound for the preoperative prediction of pathological characteristics in breast cancer - Li, Ling-Ling; Su, Quan-Li; Deng, Yun-Xia; Guo, Wen-Wen; Lun, Hai-Mei; Hu, Qiao (Frontiers in Oncology, 2024)
Objective ： To investigate the value of contrast-enhanced ultrasound (CEUS) in the preoperative prediction of the histological grades and molecular subtypes of breast cancer. Methods：183 patients with pathologically confirmed breast cancer were included. Contrast enhancement patterns and quantitative parameters were compared in different groups. The receiver operating characteristic (ROC) curve was used to analyze the efficacy of CEUS in the preoperative predicting of the pathologic characteristics, including histologic grade and molecular subtypes.Results ： The heterogeneous enhancement, perfusion defects and peripheral radial vessels were mostly observed in higher histologic grade (grade III) breast cancer. Heterogeneous enhancement and perfusion defect were the most effective indicators for grade III breast cancer, with the areas under the ROC curve of 0.768 and 0.756, respectively. There were significant differences in the enhancement intensity, post-enhanced margin, perfusion defects, and peripheral radial vessel among the different molecular subtype of breast cancer (all P < 0.01). Perfusion defects and clear edge after enhancement were the best qualitative criterion for diagnosis of HER-2 overexpressed and triple-negative breast cancer, the corresponding area under the ROC curves were 0.804 and 0.905, respectively. There were significant differences in PE, WiR, WiPI, and WiWoAUC between grade III vs grade I and II breast cancer (P < 0.05). PE, WiR, WiPI, and WiWoAUC had good efficiency in the diagnosis of high-histologic grade breast cancer. PE had the highest diagnostic efficiency in Luminal A, while WiPI had the highest diagnostic efficiency in Luminal B subtype breast cancer, with the areas under the ROC curve were 0.825, 0.838, respectively. WiWoAUC and WiR were the most accurate parameters for assessing triple-negative subtype breast cancers, with the areas under the curve were 0.932 and 0.922, respectively.Conclusion ： Qualitative and quantitative perfusion analysis of contrast-enhanced ultrasound may be useful in the noninvasive predicting of the histological grade and molecular subtypes of breast cancers.